Contamination pathways of polychlorinated biphenyls (PCBs) – From the worker to the family - Kaifie, Andrea; Schettgen, Thomas; de Hoogd, Manfred; Kraus, Thomas; Esser, Andre (International Journal of Hygiene and Environmental Health, 2019)
The improper recycling of old industrial sized capacitors and transformers in Dortmund, Germany, led to a contamination of workers and environment with polychlorinated biphenyls (PCBs). In 2010, a surveillance program was conducted for the former workers, their relatives, and residents next to the recycling company. In the human biomonitoring, elevated values for PCBs were detected in a proportion of the in-house relatives of the workers, including children. The aim of this study was to reconstruct the contamination pathways from the company to the family. Brought home working clothes of the former employees were identified as a first pathway for a contamination of the residential environment. Those clothes were cleaned at home, due to temporary employment contract. Washing machines and dryers were in consequence highly contaminated with PCBs. This led to a contamination of the relative's clothes and by this to a dermal uptake of PCBs. Another exposure pathway was the inhalation of PCB containing dust. In particular at locations, that were in contact with the working boots, high levels of PCBs were detected in the ambient monitoring. This established another exposure pathway by inhalation of PCB containing dust. The link between the residential influence factors and the PCB plasma concentration (n = 54) is shown by rank correlation. In conclusion, it should be avoided to take home potentially contaminated working clothes or boots, to prevent an exposure of children and other family members.
CRIS-Team Scopus Importer:2023-09-25
Keywords: Biomonitoring; Dermal exposure; Environmental monitoring; Inhalation exposure